Balancing Progress and Challenges: Enhancing Trust and Security in Social Networks - Srikar, Gampa Shanmukha; N. Srinivasu, N. Srinivasu (Journal of Neonatal Surgery, 2025)
The utilization of social networks as a means of communication is becoming an increasingly significant practice in this day and age, when digital technology is such an integral part of the everyday life of people all over the world. However, the prevalence of spammers and fake user accounts poses significant threats to the integrity of these platforms, as well as to the safety and trust of the users of these platforms. These threats are a direct result of the fact that spammers are easily accessible. When it comes to these dangers, which are a direct result of themselves, the prevalence of spammers is directly responsible for contributing to them. The existence of spammers in every location that has access to the internet is the root cause of these issues, which can be traced back to their presence. Through the application of a variety of strategies, we will investigate advanced methods that can be utilized to identify and eliminate spammers and fake users. These methods can be utilized to eliminate spammers and fake users. In order to accomplish the purpose of this paper, an investigation into the nature of these methods will be carried out. The investigation into these methods makes use of a wide range of social networks in order to collect information about them. The implementation of a comprehensive framework that incorporates the methods of behaviour analysis, content examination, and account attributes is something that we propose as a potential solution to the problem. This framework would be implemented in order to address the issue. The application of a wide range of academic disciplines, such as natural language processing (NLP), network analysis, and machine learning, amongst others, became feasible in order to facilitate the development of this framework. The work that was done also includes a discussion of the difficulties, ethical considerations, and potential future directions that could be taken in the fight against this issue. This discussion is included in the work that can be found here. This discussion is included as a component of the findings of the study, which are included in the findings.